Rufaida Al-Asalmiya: Florence Nightingale Muslim di Dunia Islam - Khasanah, Uswatun (Universitas Muhammadiyah Yogyakarta, 2006)
In this paper will be presented the history of nursing in Islamic society. Rufaida is the first professional nurse in Islamic history. She lived in the Prophet Muhammad (PBUH) time in the 1st century AH/8th century CE. In the history mention that she devoted her life for the society for better health. She went out to the community and tried to solve the problem the social problem that lead to disease as well as she involved in the battle to provide care to the Muslim army. She had all attributes expected of a good nurse, she was kind and empathetic. She was considered as the founder of nursing school and clinic.Pada tulisan ini disajikan tentang sejarah keperawatan dari dunia Islam. Rufaida adalah seorang perawat professional pertama dalam sejarah Islam. Beliau hidup pada masa Nabi Muhammad pada abad pertama hijriah atau abad ke 8 masehi. Didalam sejarah menyebutkan bahwa beliau mencurahkan perhatiannya kepada masyarakat untuk mencapai kesehatan yang lebih baik. Beliau mendatangi masyarakat dan mencoba mengatasi masalah social yang berhubungan dengan kesehatan. Beliau juga terlibat dalam perbagai peperangan untuk merawat tentara Muslim yang terluka. Rufaida memiliki sifat-sifat yang seharusnya dimiliki oleh seorang perawat, baik hati dan juga empati. Beliau dianggap sebagai pembangun sekolah perawat dan klinik pertama.